Análise dos atributos da atenção primária em crianças internadas por doenças evitáveis: acesso de primeiro contato e longitudinalidade - Benevides, Jéssica Lima (2017)
Primary Health Care (PHC) deals with the user's first contact with the health system. In this sense, a broad concept was proposed and directed to the presence and the extension of essential attributes and derivatives in the primary care service. In child health, hospitalizations that are sensitive to primary care are identified as preventable diseases such as pneumonia and diarrhea. OBJECTIVE: To know the attributes of primary care access to first contact and longitudinality offered to children under five years old hospitalized for conditions that are sensitive to primary care, for the diagnosis of diarrhea, pneumonia and / or asthma in the city of Fortaleza. METHODS: A cross-sectional, quantitative study, carried out in two pediatric hospitals. The population was composed of children under five years old, of both sexes, hospitalized for diagnosis of diarrhea, pneumonia and asthma, who had received care in the health or capital units in the last 12 months. Data collection was performed using the PCATool - Primary Care Assessment Tool Child version, which assesses the presence and extension of the essential attributes and derivatives of PHC in child health care services. RESULTS: 120 caregivers were interviewed and 70% of hospitalizations were due to pneumonia. The average age of the interviewees was approximately 27 years and the mothers were the respondents. The majority resided in circumscribed districts in SER V and VI of Fortaleza, 38 (31.7%). In the majority they had benefit of the social program of the federal government, Bolsa Família, 75 (62.5%). The family income of most households was only one minimum wage, 62 (51.7%). Both attributes had low scores, with the exception of the Affiliation Degree component, being the only one among all components of the instrument evaluated satisfactorily (≥6.6). It was verified that the Longitudinality attribute (> 4.0) had a lower score than First Contact Access (5,6). CONCLUSION: For the mothers and / or caregivers of children under five hospitalized for pneumonia, diarrhea and / or asthma, the attributes of APS Access First Contact and Longitudinality obtained unsatisfactory scores. Knowledge of the aspects that involve the attributes of Primary Health Care and its offer for the care of the child are extremely important, since they have the potential to provide subsidies to professionals and managers of the Unified Health System from a perspective of health services organization .